2013
DOI: 10.1371/journal.pone.0078577
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Pathway-Based Approach for Genome-Wide Association Studies: Identification of New Pathways for Rheumatoid Arthritis and Type 1 Diabetes

Abstract: Genome-wide association studies (GWAS) led to the identification of numerous novel loci for a number of complex diseases. Pathway-based approaches using genotypic data provide tangible leads which cannot be identified by single marker approaches as implemented in GWAS. The available pathway analysis approaches mainly differ in the employed databases and in the applied statistics for determining the significance of the associated disease markers.So far, pathway-based approaches using GWAS data failed to conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…We found the majority of these 33 pathways are related to immune system ( n =17), infectious diseases ( n =8), cellular processes ( n =3). Among these pathways, there are 24 pathways to be found respectively as RA-related pathways in the pervious published studies [ 2 , 21 , 23 , 24 ]. There are 18 pathways to be identified by SNP dataset and 10 novel pathways which were not reported in pervious literatures.…”
Section: Resultsmentioning
confidence: 99%
“…We found the majority of these 33 pathways are related to immune system ( n =17), infectious diseases ( n =8), cellular processes ( n =3). Among these pathways, there are 24 pathways to be found respectively as RA-related pathways in the pervious published studies [ 2 , 21 , 23 , 24 ]. There are 18 pathways to be identified by SNP dataset and 10 novel pathways which were not reported in pervious literatures.…”
Section: Resultsmentioning
confidence: 99%
“…In these pathways, six risk pathways were reported to be associated with RA in previous literatures. 6,17,18,20 This indicated that this method is effective on identifying the RA-risk pathways.…”
Section: Consistency Analysis Of Two Permutation Methodsmentioning
confidence: 87%
“…All 19 pathways had been proven to be RA-related risk pathways in the literatures. 6,7,[16][17][18]21 The results also indicated that it was effective and feasible to use all SNP to identify risk pathways.…”
Section: Consistency Analysis Of Two Permutation Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…A promising direction is to perform unbiased, large-scale integrative studies of multi -omics data as the molecular interplay among these axes remains largely underexplored. These integrative approaches have already demonstrated a potential to dissect the complexity and to identify the underlying regulators of other complex diseases such as Alzeheimer's disease (82), type I diabetes (83), and breast cancer (84) and may provide a useful strategy to fulfill these unmet needs.…”
Section: Resultsmentioning
confidence: 99%